Reason and feeling ; the challenging journey of Paulin Hountondji - KITI, PAUL CHRISTIAN (My University, 2023)
"Hountondji ? He is a white man" (Combats pour le sens. Un itinéraire africain, 1997: 172). So was he described by the great Rwandese philosopher Alexis Kagame. Many other African scholars, though they do not express it, would agree with Kagame. But who is really Hountondji ? What has been so far his main intellectual focus ? Has his commitment to the defense of reason as universality been relevant to Africa and to the world at large ? As an African, has he ever made any place for feeling and for Africa in his thought ? Those are the questions which have been examined in this reflection. The analytical and the deductive method we have used in this paper has led us to two main results. Firstly, though Hountondji is one of the most outstanding African philosophers, there is a lot of feeling in his life and in his thought. Secondly, far from being a Eurocentric thinker, Hountondji is really concerned and engaged with the well-being of the African continent.
Keywords: Reason; feeling; philosophy; ethnophilosophy; Africa